Identification Of Helicobacter Pylori Antigenic Proteins From Isolates Of Patients With Gastric Pathologies - Lee, Chun Wei (2011)

(untitled)
Helicobacter pylori is a gram negative, spiral-shaped, microaerophilic bacterium, which colonizes the apical side of human gastric epithelial cells and mucous layer. H. pylori infections are associated with various gastric diseases with wide spectrum of clinical outcomes, ranging from gastric cancer to ulceration of the gastrointestinal tract. The pathogenicity of the infection depends on the strain virulence, host susceptibility and environmental co-factors. Thus it is very important to understand the pathogenesis of the disease. Identification of the antigenic proteins of H. pylori, may eventually lead to the development of diagnostic test for this pathogen.